PERANAN PENDIDIKAN AGAMA ISLAM DALAM PEMBINAAN MORAL GENERASI MUDA - Bahmid, Narjun (Musawa: Journal for Gender Studies, 2019)
Lately, the moral condition of the younger generation is very worrying, where some of them have dared to do immoral act, thus damaging their moral. They have dared to violate the values, norms and rules of religion and government. For this reason the need for moral development of the younger generation, especially coaching through Islamic Religious Education. Islamic Religious Education is a powerful tool to overcome all problems, including the moral problems of the younger generation.